Trade-offs in pastoral governance in Norway: Challenges for biodiversity and adaptation - Risvoll, Camilla; Fedreheim, Gunn Elin; Galafassi, Diego (Pastoralism, 2016)
Published version. Source: https://pastoralismjournal.springeropen.com/articles/10.1186/s13570-016-0051-3 Norway is committed to the two-fold policy objective of preserving biodiversity and maintaining traditional local livelihoods. This creates management dilemmas with the potential to undermine the legitimacy of both national and international policies. In this article, we take a social-ecological perspective to highlight how these two policy objectives are linked and interdependent and, therefore, subjected to complex dynamics between institutions and ecosystems. We use a case study in northern Norway to discuss trade-offs in the implementation of the two-fold conservation objectives. Based on interviews, a focus group meeting with 16 reindeer herders and stakeholders and participant observations during a grazing committee meeting, we identified that ecological dynamics between carnivores, sheep and grassland patterns are central to this trade-off. We demonstrate how current governance instruments in carnivore management do not address the spatial dynamics of carnivores leading to a perceived conflict between environmentalist groups and farmers around questions of carnivore protection and sheep killings by carnivores. Fragmentation in the multi-layered governance system prevents ongoing dialogue among various actors, thereby enhancing antagonisms while reducing the likelihood of the emergence and implementation of adaptation measures and practices.